Effectiveness of Ondansetron and Metoclopramide in Management of Post-Operative Nausea and Vomiting in Laparoscopic Surgeries - Alhaaj, Abdulhakim; Ismail Alhwij,; Ali Aborkis, (AlQalam Journal of Medical and Applied Sciences, 2024)
Post-operative nausea and vomiting (PONV) is one of the most complicated and serious problems with anesthesia and surgical practices that may occur separately or in combination, and without prophylactic intervention. It is account for one third of patients under general anesthesia. This study aims to compare the efficacy of Ondansetron and Metoclopramide on post-operative nausea and vomiting in laparoscopic surgery. Data of four studies were integrated with a total number of 979 patients. Then, PONV in accordance to Ondansetron and Metoclopramide was analyzed and calculated. The results show that the incidence of PONV in metoclopramide patient’s group was (423/979) 43% and in ondansetron patient’s group was (404/979) 41%. There was no clear difference between the two groups. However, Ondansetron was slightly effective than metoclopramide in reducing PONV. يعد الغثيان والقيء من أحد أكثر المشاكل تعقيدًا وخطورة اثناء التخدير والعمليات الجراحية ان لم يكن هناك تدخل وقائي. ونسبة حدوثه قد تصل الى ثلث المرضى تحت التخدير العام. تهدف هذه الدراسة إلى المقارنة بين فعالية أوندانسيترون وميتوكلوبراميد على الغثيان والقيء بعد عمليات جراحة المناظير. تم دمج بيانات أربع دراسات بإجمالي 979 مريض. ثم تم تحليل وحساب معدل حدوث الغثيان والقيء بعد الجراحة لكل من المرضى بحسب نوع الدواء (لأوندانسيترون وميتوكلوبراميد). أظهرت النتائج أن نسبة حدوث الغثيان والقيء بعد الجراحة في مجموعة مرضى الميتوكلوبراميد كانت (423/979) 43% بينما مجموعة مرضى الأوندانسيترون كانت (404/979) 41%. لم يكن هناك فرق واضح بين المجموعتين. ومع ذلك، كان الأوندانسيترون فعالاً بشكل طفيف من الميتوكلوبراميد في تقليل حدوث الغثيان والقيء بعد الجراحة